(3QHW GdThGQO aj Md GdThGgOs - (3eMeO Hf EHQGgje Hf jhSa GdJGPaj GdMfajs; (3GdRfLGfj , YHO GdhgGH Hf EHQGgje Hf YHO GdhgGH GdNRQLj, YRGdOjf CHh GdaVGFd,J (B655 (3g` s ((3YHO Gddg Hf CMeO Hf YKeGf GdcQOi GdVheGWi GdMdHi s)
(3ChdgG (B:s
(3hHYO ajbhd GdJGPai deGcGf JUQja GdRfLGfi hTQMg ddJaJGRGfi eYJhQkG ai af GdJUQja dcf ThGgOg eaJbQI Edi JHjjf s
(3BNQgG (B:s
(3hEf cGf ZjQ MUjf hgPG BNQ eG GYJfi HLeYg s
(3GdYRi ai GdfJUQja ddRfLGfi GfXQ cTa GdXfhf L (B2 (3U` (B1139s
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdUQas